Jane Austen and William Shakespeare
XXII, 415 p. 41 illus.
Keywords: This volume explores the multiple connections between the two most canonical authors in English, Jane Austen and William Shakespeare. The collection reflects on the historical, literary, critical and filmic links between the authors and their fates. Considering the implications of the popular cult of Austen and Shakespeare, the essays are interdisciplinary and comparative: ranging from Austen’s and Shakespeare’s biographies to their presence in the modern vampire saga Twilight, passing by Shakespearean echoes in Austen’s novels and the authors’ afterlives on the improv stage, in wartime cinema, modern biopics and crime fiction. The volume concludes with an account of the Exhibition “Curating Will & Jane” at the Folger Shakespeare Library, which literally brought the two authors together in the autumn of 2016. Collectively, the essays mark and celebrate what we have called the long-standing “love affair” between William Shakespeare and Jane Austen—over 200 years and counting.